The problem of performing conditional transactions in private Blockchain-systems - Стеценко, П.И.; Халимов, Г.З. (Radiotekhnika, 2017)
The problem of performing conditional transactions is presented. This problem prevents users of the most popular Blockchain-systems from performing conditional transactions in the closed, private Blockchain ledgers. The paper discusses the links of the presented problem with other problems and shows that it is not limited to the Ethereum Blockchain technology, but it can potentially extend to the closed, private Blockchain ledgers which use proof-of-stake consensus mechanism. The problem of performing conditional transactions can lead to the loss of digital assets or double-spending attacks. A possible way to prevent this problem is to create smart-contracts instead of using usual transactions, but this will add complexity and is only applicable to systems with the Turing-complete programming language.